Maria Canella, Sergio Giuntini, Marco Turinetto (eds.), Nonostante tutto. Sport e stile. 150 anni d’immagine al femminile (Ginevra-Milano, Skira, 2011, 224 pp. ISBN 8857-211-954) (Altre Modernità, 2014)
Maria Canella, Sergio Giuntini,Marco Turinetto (eds.),Nonostante tutto. Sport e stile.150 anni d’immagine al femminile(Ginevra-Milano, Skira, 2011, 224 pp. ISBN 8857-211-954)